Yonnataa: a look at ethnomotor skills and the wayuu somatic culture (Impetus, 2021)
This research seeks to characterize the motor development and somatic Wayuu culture considering the body as a bio-psycho-social fact. In this sense, it has also been necessary to establish how the Wayuu stimulate the motor development of children in order to prepare them for the execution of tasks that guarantee subsistence (fishing, hunting, herding, agriculture, making handicrafts), leisure and recreation (indigenous and appropriate games), the reproduction of culture (dance) and the strengthening of identity. The geographical and cultural context of the Wayuu indigenous people who live in the department of La Guajira - Colombia is presented. The theoretical references are based on the approaches of the anthropology of the body, the concepts of somatic culture, ethnomotricity, motor development and motor expressions. The methodology is based on the qualitative approach, the ethnographic method and the application of techniques such as the interview and participant observation. The results present the different stages of development defined by the Wayuu and the characterization of motor development in each one of them. Likewise, the importance of some daily activities for the development of specific skills is pointed out. Somatic culture and motor development of the Wayuu must be approached from a holistic perspective and their promotion must not only contemplate the physical dimension of the individual but also the cognitive and cultural dimension. Key Words: Ethnomotricity